Advanced vibrational spectroscopy for biomedical applications: University of Cambridge, United Kingdom, 21-23 March 2016 - Gardner, Peter (Faraday discussions, 2016)
Infrared micro-spectroscopy of human tissue: principles and future promises /Max Diem [and 5 others] --Development of a practical spatial-spectral analysis protocol for breast histopathology using Fourier transform spectroscopic imaging /F. Nell Pounder, Rohith K. Reddy and Rohit Bhargava --FTIR spectroscopic imaging and mapping with correcting lenses for studies of biological cells and tissues /James A. Kimber, Liberty Foreman, Benjamin Turner, Peter Rich and Sergei G. Kazarian --Multi-centre Raman spectral mapping of oesophagael cancer tissues: a study to assess system transferability /M. Isabelle [and 13 others] --Label-free classification of colon cancer grading using infrared spectral histopathology /C. Kuepper [and 5 others] --Advancements in quantum cascade laser-based infrared microscopy of aqueous media /K. Haase, N. Kröger-Lui, A. Pucci, A. Schönhals and W. Petrich --High-throughput quantum cascade laser (QCL) spectral histopathology: a practical approach towards clinical translation /Michael J. Pilling [and 5 others] --Spectral pathology: general discussion --Raman spectroscopy for cytopathology of exfoliated cervical cells /I. R. Ramos [and 7 others] --Towards quantitative molecular mapping of cells by Raman microscopy: using AFM for decoupling molecular concentration and cell topography /Radu Boitor, Faris Sinjab, Stephanie Strohbuecker, Virginie Sottile and Ioan Notingher --Vibrational spectroscopy in sensing radiobiological effects: analyses of targeted and non-targeted effects in human keratinocytes /Aidan D. Meade [and 5 others] --Mie scatter corrections in single cell infrared microspectroscopy /Tatiana Konevskikh, Rozalia Lukacs, Reinhold Blümel, Arkadi Ponossov and Achim Kohler --Infrared imaging of small molecules in living cells: from in vitro metabolic analysis to cytopathology /Luca Quaroni, Theodora Zlateva, Katia Wehbe and Gianfelice Cinque --Chemotherapeutic response to cisplatin-like drugs in human breast cancer cells probed by vibrational microspectroscopy /A. L. M. Batista de Carvalho [and 8 others] --Single cell analysis/data handling: general discussion --Non-invasive chemically specific measurement of subsurface temperature in biological tissues using surface-enhanced spatially offset Raman spectroscopy /Benjamin Gardner, Nicholas Stone and Pavel Matousek --High resolution FTIR imaging provides automated discrimination and detection of single malaria parasite infected erythrocytes on glass /David Perez-Guaita [and 6 others] --Rapid characterization of Klebsiella oxytoca isolates from contaminated liquid hand soap using mass spectrometry, FTIR and Raman spectroscopy /Ralf Dieckmann [and 9 others] --Fiber-optic Raman spectroscopy for in vivo diagnosis of gastric dysplasia /Jianfeng Wang [and 6 others] --Investigation of intervertebral disc degeneration using multivariate FTIR spectroscopic imaging /Kerstin T. Mader [and 6 others] --Assessing corneal biomechanics with Brillouin spectro-microscopy /Guillaume Lepert, Ricardo M. Gouveia, Che J. Connon and Carl Paterson --Clinical spectroscopy: general discussion --From synthetic DNA to PCR product: detection of fungal infections using SERS /Samuel Mabbott [and 5 others] --Sheath flow SERS for chemical profiling in urine /Colleen M. Riordan, Kevin T. Jacobs, Pierre Negri and Zachary D. Schultz --Towards SERS-based point-of-care approaches for therapeutic drug monitoring: the case of methotrexate /Stefano Fornasaro, Silvia Dalla Marta, Marco Rabusin, Alois Bonifacio and Valter Sergo --SERS as a tool for in vitro toxicology /Kate M. Fisher [and 7 others] --Biofluid infrared spectro-diagnostics: pre-analytical considerations for clinical applications /L. Lovergne [and 6 others] --New IR imaging modalities for cancer detection and for intra-cell chemical mapping with a sub-diffraction mid-IR s-SNOM /H. Amrania [and 8 others] --High spatial resolution (1.1 [mu]m and 20 nm) FTIR polarization contrast imaging reveals pre-rupture disorder in damaged tendon /Richard Wiens [and 6 others] -- Biofluids and other techniques: general discussion --Translating vibrational spectroscopy into clinical applications: vision or reality? /Wolfgang Petrich.